Philosophy : a very short introduction - Craig, Edward (New York : Oxford University Press, 2002)
A brief introduction to philosophy, looking at different schools of thought and how they developed, and discussing how the work of philosophers from throughout history has shaped modern-day society.
Includes bibliographical references (p. 119-125) and index.
Adult
Keywords: Philosophy; Philosophy -- History; Philosophy; Philosophy -- History